MARKETING MANAGEMENT MIX OF PROCESSED LOCAL FOOD SNACKS AT THE NUSA HIJAU FARMER GROUP IN OESAO SUB-DISTRICT, EAST KUPANG DISTRICT, KUPANG REGENCY - Bria, Klara Seniyanti; Kapioru, Charles; Bureni, Eman Nevianus; Hendrik, Ernantje (Buletin Ilmiah Impas, 2025)
This study aims to examine the production process, marketing mix management, and income generated from local snack food processing by the Nusa Hijau Farmer Group in Oesao Village, East Kupang District, Kupang Regency. The processed products include kue nogasari made from bananas and kue ubi isi gula lempeng made from cassava. This research uses a descriptive method with a qualitative approach, supported by quantitative analysis to calculate business income. The results show that the production process is carried out traditionally using locally sourced raw materials and simple household-scale equipment, with active participation from group members. The marketing mix strategy includes: (1) Product: distinctive taste, safe for consumption, and preservative-free, but lacks innovation in packaging and product variety; (2) Price: set at IDR 1,000 per unit, based on local purchasing power and simple production costs; (3) Promotion: still limited to word-of-mouth and personal social media platforms such as WhatsApp and Facebook; (4) Distribution: conducted directly from the production site and through local orders, with no partnerships yet with souvenir shops or larger institutions. Income analysis shows total production costs of IDR 2,362,500 and revenue of IDR 4,500,000 from selling 4,500 snack units, resulting in a net income of IDR 2,137,500. The R/C Ratio value of 1.90 indicates that for every IDR 1 spent, the return is IDR 1.90, making this business profitable and feasible for further development.